In-Situ Growth of NiAl-Layered Double Hydroxide on AZ31 Mg Alloy towards Enhanced Corrosion Protection - Ye, Xin (Nanomaterials (Basel), 2018)
NiAl-layered double hydroxide (NiAl-LDH) coatings grown in-situ on AZ31 Mg alloy were prepared for the first time utilizing a facile hydrothermal method. The surface morphologies, structures, and compositions of the NiAl-LDH coatings were characterized by scanning electron microscopy (SEM), three dimensional (3D) optical profilometer, X-ray diffractometer (XRD), Fourier transform infrared spectrometer (FT-IR), and X-ray photoelectron spectroscopy (XPS). The results show that NiAl-LDH coating could be successfully deposited on Mg alloy substrate using different nickel salts, i.e., carbonate, nitrate, and sulfate salts. Different coatings exhibit different surface morphologies, but all of which exhibit remarkable enhancement in corrosion protection in 3.5 wt % NaCl corrosive electrolyte. When nickel nitrate was employed especially, an extremely large impedance modulus at a low frequency of 0.1 Hz (|Z|(f) (= 0.1 Hz)), 11.6 MΩ cm(2), and a significant low corrosion current density (j(corr)) down to 1.06 nA cm(−2) are achieved, demonstrating NiAl-LDH coating’s great potential application in harsh reaction conditions, particularly in a marine environment. The best corrosion inhibition of NiAl-LDH/CT coating deposited by carbonate may partially ascribed to the uniform and vertical orientation of the nanosheets in the coating.